Case report: A case of classic hairy cell leukemia with CNS involvement treated with vemurafenib - Johnson, Anna E.; Raju, Athul Raj; Jacob, Aasems; Hildebrandt, Gerhard C. (Frontiers in Oncology, 2023)
Hairy cell leukemia (HCL) is a rare mature B-cell lymphoproliferative disorder and most often presents as classic hairy cell leukemia. This entity is characterized by an indolent course and the presence of the BRAF V600E mutation. We report the case of an 80-year-old man with a history of classical hairy cell leukemia who presented with fatigue, dizziness, shortness of breath, blurring of vision, and headache. His initial diagnosis was 9 years prior, and he received treatments with cladribine, pentostatin, and rituximab. The workup showed an elevated white blood cell count with atypical lymphocytes, anemia, and thrombocytopenia. A peripheral blood smear confirmed HCL relapse, and a magnetic resonance imaging (MRI) of the brain showed diffuse, nonenhancing masses in the supratentorial and infratentorial regions of the brain. He was initiated on treatment with vemurafenib, with improvements in his white blood cell count and a recovery of his platelet count and hemoglobin. A repeat MRI of the brain after 3 months showed complete resolution of the lesions. Vemurafenib was discontinued after 6 months, with bone marrow biopsy showing no evidence of residual hairy cell leukemia. There have only been limited reports of HCL involvement in the central nervous system in the literature. Due to the rarity of the condition, it is not clear which treatments can be effective for intracranial disease control. Our report shows the successful use of vemurafenib, resulting in complete remission of relapsed HCL with CNS involvement.